Hemoglobin Wayne: a frameshift mutation detected in human hemoglobin alpha chains. - Seid-Akhavan, M (1976)
Hemoglobin Wayne is an alpha chain variant which manifests itself as two minor hemoglobin (Hb) components that migrate more rapidly than Hb A on electrophoresis at pH 8.6. It has been found in a child with Fanconi's anemia and in three generations of the child's family. Each of the minor components yields an alpha chain in which the carboxyl-terminal tripeptide sequence, Lys-Tyr-Arg, has been replaced by the octapeptide sequence Asx-Thr-Val-Lys-Leu-Glu-Pro-Arg. In alpha Wayne I, the slower of the pair, Asx is asparagine, whereas in alpha Wayne II it is aspartic acid. Comparison of the alpha Wayne sequences with the amino-acid sequences of alpha A and alpha Constant Spring leads to the conclusion that Hb Wayne I is the result of a -1 frameshift mutation in the alpha chain and that Hb Wayne II is formed secondarily by spontaneous deamidation of the new asparagine residue. A frameshift is consistent with a single mRNA base sequence for the last eight codons involved and supports the view of Clegg, Weatherall, and Milner [Nature (1971) 234, 337-341] that Hb Constant Spring is the result of a terminator mutation leading to translation of 31 codons not normally translated.